Perceptions of current support systems leading to international sporting success for South Africans - Mthombeni, S.; Coopoo, Y.; Noorbhai, H. (International Sports Studies, 2022)
The purpose of the study was to examine the availability of elite sport support systems of South African National Sports Federations (NSFs) and their accessibility to athletes from historically disadvantaged areas (HDA). Twenty-one NSFs from Olympic sports participated in the study whereby they responded to a questionnaire on sports policy factors leading to sporting success (SPLISS). Descriptive statistical analyses were conducted using the Statistical Package for Social Sciences (SPSS version 27.0, IBM). Informed consent was obtained from all participants before the study commenced. The majority of the NSF`s respondents reported that there was an insufficiency of financial resources, scientific and research support services, and post-sport career support. They also reported overall moderate-to-high availability of governance, organisation and sport policy structure, sport facilities, and opportunities for international competitions/exposure. Financial resources, post-career and scientific support were the most frequently reported insufficiencies, with poorer support in HDAs for all of the nine pillars of support. Additional provision is required to ensure that support systems are inclusive of athletes from HDAs. Future research needs to continue the focus on providing more detailed data on the support systems accessible to elite athletes and coaches.